SUBKLONING GEN -L-ARABINOFURANOSIDASE (abfA) DALAM VEKTOR EKSPRESI pYES2 - Wirajana, I Nengah; Wasito, Eddy Bagus; Erfan Kusuma, H.M. Soekry; Tri Puspaningsih, Ni Nyoman (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 2 Juli 2010, 2012)
A Gene encoding -L-arabinofuranosidase (abfa) that had been cloned into recombinant E. coli DH5a/pTP510 was subcloned into Saccharomyces cerevisiae yeast system. The aim of subcloning of abfA gene into S. cerevisiae is to express the thermostable -L-arabinofuranosidase (AbfA) enzyme in the host that is often termed as Generally Recognized As Safe (GRAS), so that this enzyme earn the broader application like in food and beverage industries. The gene of abfA was subcloned by the amplification of Polymerase Chain Reaction (PCR) from plasmid pTP510 templat. A pair of primers, pFSacI-Af (forward) and pXhoI-Af (reverse) from designed this research was used for the amplifcation. The PCR condition was performed as follows : beginning denaturation at 94oC for 5 min; PCR cycle 30 times that consisted of denaturation (94oC for 1 min), annealing (55oC for 30 s), and polymerization/extension at 72oC for 2 min; and than final extension at 72oC for 7 min. The abfA gene, resulted was inserted between GAL1 promoter and CYT1 terminator in the pYES2 expression vector. This ligation product was transformed into E. coli TOP10 host. Restriction analysis of recombinant plasmid from this construction, the designated as plasmid pY-Af, showed the expected size, about 7,4 kb, which was the summation of sizes of parental plasmid ( 5,9 kb) and fragment of DNA insert (1,5 kb).
Keywords: -L-arabinofuranosidase; Saccharomyces cerevisiae; subcloning, exspression vector; Polymerase Chain Reaction